KNOWLEDGE AND PRACTICES OF STAFF NURSES IN THE PREVENTION IV CANNULATION COMPLICATIONS AT ISRA UNIVERSITY HOSPITAL, HYDERABAD. (The Research of Medical Science Review, 2024)
Intravenous (IV) cannulation is a common medical procedure, but complications such as phlebitis and infiltration can lead to significant patient harm if not properly managed. This study aimed to assess the knowledge and practices of staff nurses in the Prevention of IV Cannulation Complications at ISRA University Hospital, Hyderabad. A descriptive cross-sectional study was conducted from July to September 2024, with 70 nurses selected through non-probability convenience sampling. Data was collected using a structured questionnaire, and analysis was performed using IBM SPSS Statistics Version 23. The results indicated that most nurses had good knowledge of major complications like phlebitis and infiltration. While nurses adhered well to key practices such as selecting the correct cannula and maintaining sterility, there was moderate adherence to monitoring practices post-insertion. The study highlights the need for enhanced training, especially in the early detection of complications, to further improve patient safety.